2009
DOI: 10.1016/j.bbi.2009.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Restraint stress modulates virus specific adaptive immunity during acute Theiler’s virus infection

Abstract: Multiple sclerosis (MS) is a devastating CNS disease of unknown origin. Multiple factors including genetic background, infection, and psychological stress affect the onset or progression of MS. Theiler's murine encephalomyelitis virus (TMEV) infection is an animal model of MS in which aberrant immunity leads to viral persistence and subsequently results in demyelination that resembles MS. Here, we examined how stress during acute TMEV infection altered virus-specific cell mediated responses. Using immunodomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 107 publications
4
38
0
Order By: Relevance
“…In support of this, it has been demonstrated that stress can modify T cell responses (Sommershof et al, 2010; Steelman et al, 2009). For example, Young and colleagues (submitted) demonstrate that infection related increases in virus-specific CD4+ and CD8+ T cells within the CNS are significantly attenuated due to SDR exposure.…”
Section: Discussionmentioning
confidence: 80%
“…In support of this, it has been demonstrated that stress can modify T cell responses (Sommershof et al, 2010; Steelman et al, 2009). For example, Young and colleagues (submitted) demonstrate that infection related increases in virus-specific CD4+ and CD8+ T cells within the CNS are significantly attenuated due to SDR exposure.…”
Section: Discussionmentioning
confidence: 80%
“…However, previous studies reported chronic stress increased the plasma level of IL-6and TNF-α 24, 25 , while another report showed that restraint stress caused a significant decrease in the concentrations of circulating IFN-γ, IL-12(p40), IL-12(p70), IL-4, and IL-5 26 . Recently, Smith et al .…”
Section: Discussionmentioning
confidence: 88%
“…During early infection with TMEV, RS CBA mice develop decreased NK-cell activity [33] and chemokine/cytokine expression in the brains and spleens, as well as altered viral dissemination and viral load [31,35,49] . Additionally, in SJL mice, RS suppresses virus-specific T-cell responses in the CNS as well as the periphery [50] , which may result in an exacerbated late disease [29] .…”
Section: Discussionmentioning
confidence: 99%